2021
DOI: 10.3390/su13169267
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Petroleum-Contaminated Soils with Microbial and Microbial Combined Methods: Advances, Mechanisms, and Challenges

Abstract: The petroleum industry’s development has been supported by the demand for petroleum and its by-products. During extraction and transportation, however, oil will leak into the soil, destroying the structure and quality of the soil and even harming the health of plants and humans. Scientists are researching and developing remediation techniques to repair and re-control the afflicted environment due to the health risks and social implications of petroleum hydrocarbon contamination. Remediation of soil contaminati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 161 publications
1
39
0
Order By: Relevance
“…The efficiency of the microbial degradation of hydrocarbons depends on their structure, with the intensity of biodegradation decreasing in the following series: n-alkanes → branched alkanes → low molecular weight aromatics → cycloalkanes → polycyclic aromatics [71][72][73]. Aliphatic hydrocarbons are partially oxidized by many microbes, but can be fully metabolized by only a few species (Pseudomonas, Nocardia, Xanthomonas, Bacterium, Corynebacterium, Mycobacterium, Acinetobacter) [72,74].…”
Section: Phytoremediation Of Oil-polluted Soilsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of the microbial degradation of hydrocarbons depends on their structure, with the intensity of biodegradation decreasing in the following series: n-alkanes → branched alkanes → low molecular weight aromatics → cycloalkanes → polycyclic aromatics [71][72][73]. Aliphatic hydrocarbons are partially oxidized by many microbes, but can be fully metabolized by only a few species (Pseudomonas, Nocardia, Xanthomonas, Bacterium, Corynebacterium, Mycobacterium, Acinetobacter) [72,74].…”
Section: Phytoremediation Of Oil-polluted Soilsmentioning
confidence: 99%
“…Over 100 genera of bacteria, yeast and mycelial fungi are currently known to be able to degrade hydrocarbons (Table 3). According to the literature data, the proportion of petroleum subject to biodegradation varies from 6% [76] to 82% [77] for soil fungi, and from 0.13% [76] to 100% [73,78] for bacteria. High molecular weight polycyclic aromatics can be degraded, albeit rather inefficiently, by specific microbes, with some compounds not being prone to degradation at all [52,[79][80][81].…”
Section: Phytoremediation Of Oil-polluted Soilsmentioning
confidence: 99%
“…For the phytoremediation process, certain plants and their soil-associated microorganisms are sought to detoxify the contaminants present at the rhizosphere level ( 3 ). Some studies have shown that bacteria of the genus Gordonia are useful for remediating diesel-contaminated soils ( 4 ). Gordonia sp.…”
Section: Announcementmentioning
confidence: 99%
“…Effective ways in the reclamation of contaminated soil are sought and developed in order to protect the natural environment. There are several remediation technologies applied to such soils whose aim is to contain, immobilise, and remove pollutants using physical, chemical, and biological processes [ 31 ]. One of the solutions consists of the application of different mineral and organic materials in the phytostabilisation process, which have a positive effect on the properties of soil and growth of plants [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%